2009
DOI: 10.1111/j.1471-4159.2009.06355.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective modulation of amyloid‐β peptide degradation by flurbiprofen, fenofibrate, and related compounds regulates Aβ levels

Abstract: Gamma‐secretase modulators (GSMs) include selected non‐steroidal anti‐inflammatory drugs such as flurbiprofen that selectively lowers the neurotoxic amyloid‐β peptide Aβ1–42. GSMs are attractive targets for Alzheimer’s disease, in contrast to ‘inverse GSMs,’ such as fenofibrate, which selectively increase the level of Aβ1–42. A methodology for screening of Aβ modulating drugs was developed utilizing an Aβ‐producing neuroblastoma cell line stably transfected with mutant human amyloid precursor protein, immunopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 72 publications
(84 reference statements)
3
18
0
Order By: Relevance
“…In contrast, fibric acid, the free acid form of 39 was reported to lower the levels of Aβ 1–42 . 16 A similar observation on Aβ 1–42 modulation was made herein with 1 and its ester, 38 . Whereas, the ester acted as a SARA, the free acid, 1 at 100 µM, selectively lowered Aβ 1–42 and elevated Aβ 1–37 relative to the vehicle control (Fig.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…In contrast, fibric acid, the free acid form of 39 was reported to lower the levels of Aβ 1–42 . 16 A similar observation on Aβ 1–42 modulation was made herein with 1 and its ester, 38 . Whereas, the ester acted as a SARA, the free acid, 1 at 100 µM, selectively lowered Aβ 1–42 and elevated Aβ 1–37 relative to the vehicle control (Fig.…”
Section: Resultssupporting
confidence: 81%
“…4143 In order to study the effect of agents on amyloidogenesis in more detail, we determined the profile of Aβ fragment production from N2a.hAPP cells for selected compounds using an immunoprecipitation MALDI-TOF technique introduced in 2009. 16 This technique quantifies the amyloid fragments Aβ 1–37 , Aβ 1–38 , Aβ 1–40 , and Aβ 1–42 , using Aβ 1–43 as an internal standard, since this fragment is not a product of amyloidogenesis. In the N2a.hAPP amyloidogenesis assay, we observed that the known SARA 39 (200 µM) increased Aβ 1–42 levels threefold but had modest effects on Aβ 1–37 and Aβ 1–38 , although lowering the level of the latter fragment (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study provided another mode of action for so-called secretase modulators 48 . While developing a methodology for screening drugs that can decrease Aβ levels, Abdul-Hay et al found that some -secretase modulators altered Aβ levels in the media even in the absence of cells.…”
Section: Unexpected Modes Of Action For --Secretase Modulatorsmentioning
confidence: 99%